2021
DOI: 10.4103/ijo.ijo_3529_20
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetic retinopathy on pulse wave analysis-derived arterial stiffness and hemodynamic parameters: A cross-sectional study from Gujarat, India

Abstract: Purpose: Type 2 diabetes mellitus (T2DM) is known to produce diabetic retinopathy (DR). Pulse wave analysis (PWA) provides arterial stiffness (AS) and central hemodynamic (CH) parameters. We studied the effect of DR on AS and CH parameters in type 2 diabetics (T2D). Methods: We performed a cross-sectional study on 47 T2Ds attending a private ophthalmology clinic screened for DR by optical coherence tomography angiography and divided into NDR (non-DR), NPDR (non-prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…[ 4 6 ] However, few studies did not find any association between central aortic stiffness and T2DM retinopathy. [ 13 14 ] In the present study, baPWV was found to be significantly higher in T2DM patients with retinopathy than in T2DM patients without retinopathy. Moreover, a positive association of baPWV with the T2DM retinopathy group was found.…”
Section: Discussionsupporting
confidence: 52%
“…[ 4 6 ] However, few studies did not find any association between central aortic stiffness and T2DM retinopathy. [ 13 14 ] In the present study, baPWV was found to be significantly higher in T2DM patients with retinopathy than in T2DM patients without retinopathy. Moreover, a positive association of baPWV with the T2DM retinopathy group was found.…”
Section: Discussionsupporting
confidence: 52%